Assessment of Preoperative and Postoperative Dental Anxiety among Dental Patients in Kanyakumari District - L, Beryl. P.; Arunmozhi, A. ,; Glory, Sr. Agnes (International Journal of Psychosocial Rehabilitation, 2020)
The dental awareness plays a main role in anxiety of the person during dental treatment. People are more anxious during dental treatment. Researcher has chosen the study area for the present study as Kanyakumarai District which is in southern part of Tamilnadu. Objectives of the study is to evaluate the preoperative and postoperative anxiety among the dental patients and also suggest solutions to the psychological problems faced by the dental patients before and after treatment The tool used is Dental Concerns Assessment Scale, Clarke & Rustvold (1993) for measuring anxiety level of dental patients before and after treatment. The questionnaire for the study was conducted on a small population consisting of 370 dental patients randomlyAfter treatment the anxiety level is low and moderate. To reduce the anxiety level the dentists should give proper orientation and motivation.